E-commerce and wealth management service - Quader, Mohammed Shahedul; Siddique, M. Abu Bakar; Ahmed, Ezaz (BRAC University, 2010)
The aim of this paper is to identify wealth management services and the impact that e-commerce has had upon its range and delivery. The study reveals that e-commerce undoubtedly provides technological opportunities to expand services and introduce new and sometimes innovative tools and functions to enhance client relationships. However, it is found not to be a panacea, with improved client and relationship manager supplied information more critical to success. It also considers the impact of e-commerce on CRM where attempts at segmentation have met with mixed results and client needs are still to be effectively served as a whole.